2014
DOI: 10.1111/medu.12282
|View full text |Cite
|
Sign up to set email alerts
|

What is appropriate to post on social media? Ratings from students, faculty members and the public

Abstract: The most significant conclusion of our study is that faculty members, medical students and the 'public' have different thresholds of what is acceptable on a social networking site. Our findings will prove useful for students to consider the perspectives of patients and faculty members when considering what type of content to post on their social media sites. In this way, we hope that our findings provide insight for discussions, awareness and the development of guidelines related to online professionalism for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 16 publications
3
65
0
2
Order By: Relevance
“…An online survey utilizing mock Facebook profiles found that, compared to university students, faculty and members of the general public rated images significantly less appropriate. 15 Our findings are consistent with prior evidence: a high level of consensus for investigation in themes involving confidentiality, inappropriate communication, and discrimination, and a low consensus for themes associated with social identity, including derogatory speech and images of alcohol (with and without intoxication). Our results suggest there remains a disconnect in the perceived risk of unprofessional SM behaviors related to social identity in EM in all positions, including students, residents, and attending physicians.…”
supporting
confidence: 89%
“…An online survey utilizing mock Facebook profiles found that, compared to university students, faculty and members of the general public rated images significantly less appropriate. 15 Our findings are consistent with prior evidence: a high level of consensus for investigation in themes involving confidentiality, inappropriate communication, and discrimination, and a low consensus for themes associated with social identity, including derogatory speech and images of alcohol (with and without intoxication). Our results suggest there remains a disconnect in the perceived risk of unprofessional SM behaviors related to social identity in EM in all positions, including students, residents, and attending physicians.…”
supporting
confidence: 89%
“…The posting practices of these superusers align with guiding principles of online professionalism derived from national consensus statements and guidelines, 20,21 research on stakeholders' perspectives of what is appropriate and what is inappropriate to post, [22][23][24][25] and expert opinion. 6,26 These include safeguarding patient privacy, Bpause before posting,^avoiding inflammatory material, and carefully considering material that is to be posted for public consumption.…”
Section: Discussionmentioning
confidence: 92%
“…A recent survey among medical students showed that there is little consensus on what constitutes unprofessional behavior beyond the US Health Insurance Portability Act violations and students have felt that posting inappropriate material on personal social media sites was “unavoidable” [8,9]. Furthermore, studies have reported that students are unaware of ethical concerns posed by social media usage [10]; and even if students are aware of the importance of online professionalism, they do not feel it is relevant to them until they graduate and have an actual online professional identity [11].…”
Section: Introductionmentioning
confidence: 99%
“…Although focus groups, surveys, and reviews of the literature have gathered usage information and perspectives from medical students and doctors [8,16,17], including a study that gathered information on health science students’ media preferences and how often they use social media sites, and evaluated their responses to advertisements [18], no study to our knowledge, has examined the user profiles, attitudes, and perspectives of students from multiple disciplines and multiple cultures on the use of social media in health science education. Understanding the demographics and perceptions of students in different health science disciplines may be imperative to developing better student guidelines.…”
Section: Introductionmentioning
confidence: 99%